Prognostic Impact of Muscle Quantity and Quality and Fat Distribution in Diffuse Large B-Cell Lymphoma Patients - Besutti, Giulia; Massaro, Fulvio; Bonelli, Efrem; Braglia, Luca; Casali, Massimiliano; Versari, Annibale; Ligabue, Guido; Pattacini, Pierpaolo; Cavuto, Silvio; Merlo, Domenico F.; Luminari, Stefano; Merli, Francesco; et al. (Frontiers in Nutrition, 2021)
Baseline CT scans of 116 patients (48% female, median 64 years) with diffuse large B-cell lymphoma (DLBCL) were retrospectively reviewed to investigate the prognostic role of sarcopenia and fat compartment distributions on overall survival (OS), progression-free survival (PFS), and early therapy termination. Skeletal muscle index (SMI), skeletal muscle density (SMD), and intermuscular adipose tissue (IMAT) were quantified at the level of the third lumbar vertebra (L3) and proximal thigh (PT). Low L3-SMD, but not low L3-SMI, was associated with early therapy termination (p=0.028), shorter OS (HR=6.29; 95% CI=2.17-18.26; p<0.001), and shorter PFS (HR=2.42; 95% CI=1.26-4.65; p=0.008). After correction for sex, International Prognostic Index (IPI), BMI, and R-CHOP therapy (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone), low L3-SMD remained associated with poor OS (HR=3.54; 95% CI=1.10-11.40; p=0.034) but not with PFS. Increased PT-IMAT was prognostic for poor OS and PFS after correction for sex, IPI, BMI, and R-CHOP therapy (HR=1.35; CI=1.03-1.7; p=0.03, and HR=1.30; CI=1.04-1.64; p=0.024, respectively). Reduced muscle quality (SMD) and increased intermuscular fat (IMAT), rather than low muscle quantity (SMI), are associated with poor prognosis in DLBCL, when measured at the L3 level, and particularly at the level of the proximal thigh. The proximal thigh represents a novel radiological landmark to study body composition.